Optimalisasi Fasilitas Gudang CFS (Container Freight Station) Terhadap Proses Behandle di PT. Terminal Teluk Lamong Surabaya - Dian Utari Maharani; Andy Wahyu Hermanto (Politeknik Ilmu Pelayaran Semarang, 2020)
Optimized CFS warehouse for stripping stuffing activities of LCL container goods, however, because PT. Teluk Lamong Terminal wants to reduce the Dwelling Time figure so that the stripping stuffing activity of LCL containers is not carried out in the CFS warehouse. Then, because there were no activities in the CFS warehouse, PT. Teluk Lamong Terminal utilizes the CFS Warehouse for container physical inspection activities (behandle). This study aims to determine the CFS warehouse facilities that can support the behandle process, determine the factors that affect the behandle process and determine the efforts that can be made to overcome the limitations of the CFS warehouse facilities during the behandle process.Researchers use qualitative descriptive methods to describe and describe the object under study. Researchers are involved in the process of searching for data by directly observing and analyzing the facts and characteristics of the object and subject under study. Sources of data used in this study are primary and secondary data. In addition, this study also uses data collection methods by means of observation, interviews, documentation, literature study. Researchers use direct and indirect observation. The results of the study concluded that the CFS warehouse facility could be used to support the behandle process at PT. Lamong Bay Terminal Surabaya. However, the physical inspection was not fully carried out in the warehouse area because the warehouse building design was not suitable for inspection activities so that the behandle was carried out outside the warehouse area and then loaded the cargo into the warehouse using a forklift. Factors that hinder behandle activities include Internal & External Factors. Efforts that can be made to optimize behandle activities are by renovating warehouses, preparing supporting facilities for inspection of goods, and preparing competent human resources.